The Arabic language, the struggle of languages, and the challenges of the cultural identity - Jasim, Thair H. (Al-Adab Journal, 2021)
The Arabic language is a specialty that distinguishes it from other languages of nations, it is the language of the Holy Qur’an, which has been closely linked to it, We have dropped it down as an Arabic Qur’an, perhaps you may be reasonable (Joseph: 2), which is still used with its voices, words, and rules to this day, and was deservedly the language of arts, science, and the arts. Each language is closely normative linked to the civilized construction of its nation and is a title of its personality and identity, and a tool for expressing ideas and feelings, a means of understanding, learning, developing, and transmitting experiences. It is the language that transforms individuals from a human group into an interconnected cultural group because it works on the cohesion of social construction, and the interdependence of the people of one nation in two dimensions: the spatial spread of spaced places, and the Tasmanian, which is the communication of subsequent generations with previous generations. Today, and also tomorrow, the Arabic language faces a real and fierce challenge, which it is obliged to deal with intelligently and intelligently, and the biggest challenge that will face the Arabic language in the future is to preserve its peculiarities and ensure its continuity and radiance, and to protect the components, components, and values that form the essential elements of the great Arab-Islamic entity. This calls for attention to the Arabic language, learning, and mastery, working hard to spread it in all fields and at all levels, and addressing its problems in the age of globalization, not only a legitimate need but a cultural and cultural necessity.